European Neuromuscular Centre consensus statement on anaesthesia in patients with neuromuscular disorders. (14th September 2022) - van den Bersselaar, Luuk R.; Heytens, Luc; Silva, Helga C. A.; Reimann, Jens; Tasca, Giorgio; Díaz‐Cambronero, Óscar; Løkken, Nicoline; Hellblom, Anna; Hopkins, Philip M.; Rueffert, Henrik; Bastian, Börge; Vilchez, Juan Jesus; et al.
Abstract: Background and purpose: Patients with neuromuscular conditions are at increased risk of suffering perioperative complications related to anaesthesia. There is currently little specific anaesthetic guidance concerning these patients. Here, we present the European Neuromuscular Centre (ENMC) consensus statement on anaesthesia in patients with neuromuscular disorders as formulated during the 259th ENMC Workshop on Anaesthesia in Neuromuscular Disorders. Methods: International experts in the field of (paediatric) anaesthesia, neurology, and genetics were invited to participate in the ENMC workshop. A literature search was conducted in PubMed and Embase, the main findings of which were disseminated to the participants and presented during the workshop. Depending on specific expertise, participants presented the existing evidence and their expert opinion concerning anaesthetic management in six specific groups of myopathies and neuromuscular junction disorders. The consensus statement was prepared according to the AGREE II (Appraisal of Guidelines for Research & Evaluation) reporting checklist. The level of evidence has been adapted according to the SIGN (Scottish Intercollegiate Guidelines Network) grading system. The final consensus statement was subjected to a modified Delphi process. Results: A set of general recommendations valid for the anaesthetic management of patients with neuromuscular disorders in general have been formulated. Specific recommendations were formulated for (i) neuromuscular junction disorders, (ii) muscle channelopathies (nondystrophic myotonia and periodic paralysis), (iii) myotonic dystrophy (types 1 and 2), (iv) muscular dystrophies, (v) congenital myopathies and congenital dystrophies, and (vi) mitochondrial and metabolic myopathies. Conclusions: This ENMC consensus statement summarizes the most important considerations for planning and performing anaesthesia in patients with neuromuscular disorders. Abstract : This consensus statement summarizes the most important recommendations concerning anaesthesia in patients with neuromuscular disorders.